Morbidity profile of preschool children in rural area of central Madhya Pradesh - Shinde, Mohan; Joshi, Ankur; Trivedi, Anshuli (International Journal Of Community Medicine And Public Health, 2017)
Background: The children of Preschool age are a vulnerable or special risk group in any population, deserving special health care. Major causes of death in the age group 0-5 years are preventable. Objective of this study was to study the morbidity profile of preschool children (0-5 years) in the rural areas and its association with some selected variables. Methods:A cross sectional study was conducted among preschool children of rural areas for a period of 4 months. A sample size of total 400 children was selected and the children were examined after interviewing mother. Results: Morbidity was found in 217 out of total 400 children. The male and female ratio of morbid children was 1.47:1. The respiratory infections and diarrheal diseases together accounted for 76.5% of children at least once in three month. Conclusions:Communicable diseases were the commonest cause of morbidity in the preschool children. A total of 164 children were found having one of the episodes of illness in last three month.